HYDROPYROLYSIS OF INSOLUBLE CARBONACEOUS MATTER IN THE MURCHISON METEORITE: NEW INSIGHTS INTO ITS MACROMOLECULAR STRUCTURE - Sephton M.A.; Love G.D.; Watson J.S.; Verchovsky A.B.; Wright I.P.; Snape C.E.; Gilmour I. (My University, 2004)
The major organic component of carbonaceous chondrites is a solvent-insoluble, high molecular weight macromolecular material that constitutes at least 70% of the total organic content in these meteorites. Analytical pyrolysis is often used to thermally decompose macromolecular organic matter in an inert atmosphere into lower molecular weight fragments that are more amenable to conventional organic analytical techniques. Hydropyrolysis refers to pyrolysis assisted by high hydrogen gas pressures and a dispersed catalytically-active molybdenum sulfide phase. Hydropyrolysis of meteorites has not been attempted previ- ously although it is ideally suited to such studies due to its relatively high yields. Hydropyrolysis of the Murchison macromolecular material successfully releases significant amounts of high molecular weight PAH including phenanthrene, carbazole, fluoranthene, pyrene, chrysene, perylene, benzoperylene and coronene units with varying degrees of alklyation. Analysis of both the products and residue from hydropyrolysis reveals that the meteoritic organic network contains both labile (pyrolysable) and refractory (nonpyrolysable) fractions. Comparisons of hydropyrolysis yields of Murchison macromolecular materials with those from terrestrial coals indicate that the refractory component probably consists of a network dominated by at least five- or six-ring PAH units cross-linked together. Copyright © 2004 Elsevier Ltd